Transport Study of Metal Cations Through a Bulk Liquid Membrane Using Benzo-18-crown-6 as an Ionophore. - ROUNAGHI, G.H.; ARBAB-ZAVAR, M.H.; FAHMIDEH-RAD., E. (Asian Journal of Chemistry, 2010)
The transport experiments of Cr3+, Co2+, Cu2+, Zn2+, Cd2+, Ag+ and Pb2+ metal cations were carried out by benzo-18-crown-6 (B18C6) using chloroform (CHCl3), 1,2-dichloroethane (1,2-DCE), dichlorometh-ane (DCM), nitrobenzene (NB), chloroform-nitrobenzene (CHCl3-NB) and chloroform-dichloromethane (CHCl3-DCM) binary mixed solvents as liquid membranes. The aqueous source phase consisted of a buffer solution (CH3COOH/CH3COONa) at pH = 5 and containing an equimolar mixture of these 7 metal cations. The organic phase contained the macrocycle ligand, benzo-18-crown-6 (B18C6) as an ionophore and the receiving phase consisted of a buffer solution (HCOOH/HCOONa) at pH = 3. The obtained results show that benzo-18-crown-6 is a highly selective ionophore for Pb2+ cation. The sequence of transport efficiency for Pb2+ cation in organic solvents was found to be : DCM > NB > 1,2-DCE > CHCl3. The influence of the stearic acid, palmitic acid and oleic acid in the membrane phase on the ion transport was investigated. A non-linear behaviour was observed for variation of the transport rate of Pb2+ cation vs. the composition of CHCl3-NB and CHCl3-DCM binary mixtures.